Effect of levothyroxine replacement therapy in patients with subclinical hypothyroidism and chronic heart failure: A systematic review - Triggiani, Vincenzo; Cittadini, Antonio; Lisco, Giuseppe (Frontiers in Endocrinology, 2022)
Background. Chronic heart failure (CHF) affects the health care system with high social and economic costs due to recurrent hospital admissions or frequent ambulatory reassessments. Subclinical hypothyroidism (SCH) is commonly observed in patients with CHF, and negatively affect myocardial function, remodeling, and, ultimately, increase the risk of hospitalizations, all-cause and cardiovascular (CV) mortality. The role of levothyroxine replacement on relevant CV outcomes in patients with SCH and CHF is unclear. Objective. To assess the effect of levothyroxine compared to placebo or no treatment on all-cause and CV mortality, major adverse CV events, and heart failure. Methods. PubMed/MEDLINE, Cochrane Library, and ClinicalTrial.gov were searched for randomized clinical trials, non-randomized observational studies, multicentric studies, and comparative studies. No language restrictions were included. After duplicate removal, articles were screened and extracted for the synthesis according to a hierarchical strategy that included title, abstract, and full-text appraisal. Risk of bias was assessed by RoB2 and ROBIN-I tools. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology was applied to rate the quality of evidence and grade strength of recommendations. Results. Two trials were included in the systematic review with considerable indirectness and inaccuracy that down-graded the level of evidence. Discussion. No evidence supports the use of levothyroxine for treating SCH in CHF due to the lack of reliable and well-designed clinical trials. Conclusion. CV outcome trials and dose-response trials are needed to better understand the role of levothyroxine replacement treatment for a safer prescription in this clinical setting.